2013
DOI: 10.1038/ejcn.2013.173
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing thyroid volume in Chinese children

Abstract: BACKGROUND/OBJECTIVES:This paper aims to compare children's thyroid volume (Tvol) by age and gender in Zhejiang province in order to explore the factors influencing Tvol in this area.SUBJECTS/METHODS:This survey was a cross-sectional survey of a provincial representative sample of Zhejiang province children aged 6–12 years. The children were asked to provide a urine sample for the determination of urinary iodine concentration (UIC) and thyroid ultrasonography was performed for the determination of Tvol.RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 4 publications
7
27
1
3
Order By: Relevance
“…Similar results have also been reported elsewhere (31). The WHO has developed criteria for defining TGR in children based on BSA, age, and sex (16,19), whereas the criteria in China were according to age (5).…”
Section: Discussionsupporting
confidence: 74%
“…Similar results have also been reported elsewhere (31). The WHO has developed criteria for defining TGR in children based on BSA, age, and sex (16,19), whereas the criteria in China were according to age (5).…”
Section: Discussionsupporting
confidence: 74%
“…Among 6 regions in the world, children in Japan, as representatives of the Asian region, had both the largest age-adjusted thyroid volumes and the largest body surface area-adjusted thyroid volumes. After publishing these data, recent studies on thyroid volume confirmed the international reference values although the number of cases are small (approximately 200-5000 cases) in all studies [11][12][13][14][15][16]. In Japan, Fuse et al compared the international reference values for Japanese and thyroid volumes of approximately 1000 schoolchildren [11].…”
Section: Discussionmentioning
confidence: 79%
“…The volume of the thyroid is influenced by age, gender, body mass index (BMI), lean body mass, iodine intake, and genetic factors (3)(4)(5). Post-mortem thyroid examination of individuals aged ≥ 50 years (6) and confirmed in centenarians (7) has identified progressive atrophy, fibrosis, increased adipose tissue, and decreased follicles and colloid, contributing to a decrease in the volume of the gland with aging (8).…”
Section: Introductionmentioning
confidence: 99%